Proceedings of the Eighth Italian Conference on Computational Linguistics CliC-it 2021 Milan, Italy, 26-28 January, 2022 - Fersini, Elisabetta; Passarotti, Marco; Patti, Viviana (Collana dell'Associazione Italiana di Linguistica Computazionale, 2022)
The eighth edition of the Italian Conference on Computational Linguistics (CLiC-it 2021) was held at Università degli Studi di Milano-Bicocca from 26th to 28th January 2022. After the edition of 2020, which was held in fully virtual mode due to the health emergency related to Covid-19, CLiC-it 2021 represented the first moment for the Italian research community of Computational Linguistics to meet in person after more than one year of full/partial lockdown.